Herpes Associated Erythema Multiforme: A Case Report (BIRDEM Medical Journal, 2017)
Herpes associated erythema multiforme (HAEM) is an acute exudative dermatic and mucosal disease caused by the Herpes simplex virus (HSV). It is the result of cell mediated immune reaction due to HSV antigen and has a presentation quite similar to Steven Johnsons Syndrome (SJS). Unlike SJS, use of steroids is not recommended in HAEM as it can aggravate the condition. Here we report a case of HAEM in a 35-year- old gentleman, who presented with fever, rash and sore throat. The clinical findings were in favour of HAEM and patient showed optimum response to symptomatic treatment.Birdem Med J 2017; 7(1): 72-75